Promoting Seafarers' Wellbeing: Addressing Psychosocial Risks in Indonesian Maritime Industry - Hesti Ekawati (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
This research investigates psychosocial risks among Indonesian seafarers and proposes Occupational Safety and Health (K3) interventions. Data from 50 cadets at the Maritime Institute of Jakarta reveal significant challenges, including isolation, long working hours, accidents at sea, stress, and fatigue. Analysis highlights the importance of promoting mental health, stress management training, and adherence to international standards. Findings underscore the need for targeted interventions and collaboration among stakeholders to create a safer and more supportive work environment for seafarers, ensuring their health and wellbeing in the Indonesian maritime industry and beyond.